The experience of disagreement between students and supervisors in PhD education: a qualitative study - Gunnarsson, Ronny (BioMed Central, 2013)
BACKGROUND: PhD supervision is mostly individual and disagreement between supervisors and PhD students is a seldom-discussed topic at universities. The present study aimed to describe the experience of disagreement between PhD students and supervisors. METHODS: Nine supervisors and seven PhD students from Sweden and England were interviewed using a video recorder. The recorded material was analysed using inductive content analysis. RESULTS: Disagreements in PhD education can be described with the overarching theme: the nature of the disagreements changes over time. Five categories emerged to describe the variations of the experiences: involvement in important decisions, supervisors not being up-to-date, dubious advice from supervisors, mediating between supervisors, and interpersonal relationships. CONCLUSIONS: There is a gradual shift in competence where PhD students may excel supervisors in subject knowledge. Early disagreements may indicate immaturity of the student while disagreements later may indicate that the student is maturing making their own decisions. Consequently, disagreements may need to be addressed differently depending on when they occur. Addressing them inappropriately might slow the progressions and result in higher attrition rate among PhD students. The five categories may be elements in future PhD supervisor training programs and should be further evaluated for their importance and impact on PhD education.